The Relationship Between Mother's History of Anemia and Chronic Energy Deficiency (CED) and The Incidence of Stunting in Toddlers Aged 0–59 Months - Indah, Louise Kartika; Tampubolon, Christine Handayani (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Child growth and development are affected by stunting, a chronic nutritional problem that occurs primarily in communities with low nutritional levels. Maternal nutritional status during pregnancy is a major cause of stunting, including anemia and chronic energy deficiency. Objective:to determine the relationship between maternal anemia and CED history on stunting in toddlers aged 0–59 months. Method: The following study used an analytical design with a retrospective approach. Data were obtained from medical records at the Welamosa Community Health Center and analyzed using the Chi-Square test and logistic regression. Result and Discussion: Of the 147 respondents, 70.7% of toddlers experienced stunting. The analysis results showed that maternal anemia had a significant relationship with stunting (p-value = 0.000, OR = 6.507). CED in mothers also showed a significant relationship with stunting (p-value = 0.008, OR = 3.676). Multivariate analysis showed that anemia was the most dominant factor in stunting compared to CED. Mothers with a history of anemia and chronic kidney disease (CED) are at higher risk of giving birth to stunted children. Conclusions: more optimal nutritional interventions for pregnant women are needed through education, iron supplementation, and regular nutritional status monitoring to prevent stunting and improve maternal and child health